Analysis of Building Platform Inhomogeneities in PBF-LB/M Process on Alloy 718 - Niccolò Baldi; Lokesh Chandrabalan; Marco Manetti; Alessandro Giorgetti; Gabriele Arcidiacono; Paolo Citti; Marco Palladino (Applied Sciences)
Additive Manufacturing (AM) processes, particularly PBF-LB/M, are considered advantageous due to their flexibility, which allows process engineers to design and fabricate intricate structures both in the prototyping and component manufacturing phases. It is well known that the behavior of the process directly impacts the quality of the materials and thereby induces inhomogeneities on the powder bed on the building platform. Several parameters can be tuned to keep the process under control, getting rid of process uncertainty and distinguishing aspects of a specific machine model. Such behavior requires an extended analysis of the powder bed inhomogeneities and the definition of limits in the printing process. In this work, carried out on Alloy 718 specimens printed using an EOS M290 machine, the inhomogeneities of the melt pool stability, density, and material properties were investigated based on three main factors: the amount of area melted or fused, the gas flow speed setpoint, and the location on the building platform. The test results for Track Stability, melt-pool shape, and porosity analysis show that criticality occurs when more than 50% of the building platform is exposed. This can be partly fixed by raising the differential pressure value.